Confluências de axé nas instituições científicas: acontecimentos para pensar práticas de conhecimento - Elisa Sampaio de Faria (2020)
In an etho-ecological perspective to approach knowledge practices, this thesis associates, in a transversal manner, emblematic events with science practitioners and practitioners of axé in Minas Gerais and Piauí, Brazil. The experiences that allowed the configuration of this text happened, especially, in encounters with practitioners of african traditions within the Knowledge Encounters program at the Federal University of Minas Gerais, institutionally called T ransversal Training in Traditional Knowledge. The field research was configured as a new experience that, assumed in its scientific sense, was characterized as a trajectory of strong learning. Cultivating of epistemic disconcertment and the art of paying attention trough this learning trajectory allowed something rare: the possibility of the production of knowledge that articulates divergent worlds without losing sight of its borders, breaking the limit on what would be possible for a practitioner of the sciences to feel, think, do and create. Guided by the events on a cosmopolitical ethnography, we created ways of situated and scientific ways of knowing that made it possible to transform the limits of the sciences into borders and to think about objectivity and ethics as constituent dimensions of science practice. Finally, the strength of the confluences at the frontiers between science and axé subverted the opposition between different knowledge practices and reactivated attachments between us, practitioners of sciences and practitioners of axé, inspiring us on the great work to be done to create knowledge practices that respect differences, and to take care of our extraordinarily alive and heterogeneous existential territories.